Efektivitas Terapi Kombinasi Metformin dan Glimepiride pada Pasien Diabetes Mellitus Tipe 2 : Tinjauan Literatur - Desak Nandini Prameswari Pagedongan; Ketut Widyani Astuti (STIKES Columbia Asia Medan, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia due to insulin resistance, decreased insulin secretion, or a combination of both. The burden of this disease continues to increase globally, making effective, safe, and affordable management an urgent need. One widely used therapeutic strategy is the fixed-dose combination (FDC) of metformin and glimepiride. This combination is considered beneficial because the two drugs complement each other in their mechanisms of action: metformin reduces hepatic glucose production and increases insulin sensitivity, while glimepiride stimulates insulin secretion from pancreatic β-cells. Furthermore, the use of FDC can simplify the treatment regimen, thereby improving patient adherence to long-term therapy. Article searches were conducted through Google Scholar and PubMed with the keywords